The Construction of Preference 2006
DOI: 10.1017/cbo9780511618031.027
|View full text |Cite
|
Sign up to set email alerts
|

Introspecting About Reasons Can Reduce Post-Choice Satisfaction

Abstract: This study tested the prediction that introspecting about the reasons far one's preferences would reduce satisfaction with a consuÂ¥merchoice Subjects evaluated two types ofposters and then chose one to take home. Those instruefed to think about their reasons chose a different type of poster than control subjects and, when contacted 3 weeks later, were less sattsfied with their choice. When People think about reasons, they appear to focus on attributes of thestimulus that are easy to verbalize and seem like pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
222
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 150 publications
(247 citation statements)
references
References 0 publications
21
222
1
3
Order By: Relevance
“…These motives often provide a better guide to behavior than does conscious and presumably rational analysis of a single current instance, which may be ignorant of base rates and prior automatic actions. This supposition accords with research by T. D. Wilson (e.g., T. D. Wilson & Schooler, 1991 ;T. D. Wilson et al, 1993 ), which demonstrates that people's "gut level" feelings are often more effective guides to action and lead to more subsequent satisfaction than do their reasoned reflections, which can interfere with emotion-based judgments.…”
Section: Unconscious Motivationsupporting
confidence: 85%
“…These motives often provide a better guide to behavior than does conscious and presumably rational analysis of a single current instance, which may be ignorant of base rates and prior automatic actions. This supposition accords with research by T. D. Wilson (e.g., T. D. Wilson & Schooler, 1991 ;T. D. Wilson et al, 1993 ), which demonstrates that people's "gut level" feelings are often more effective guides to action and lead to more subsequent satisfaction than do their reasoned reflections, which can interfere with emotion-based judgments.…”
Section: Unconscious Motivationsupporting
confidence: 85%
“…Specifically, conscious reflection can reduce the quality of choices and post-choice satisfaction (Wilson & Schooler, 1991;Wilson et al, 1993); it can produce suboptimal decisions (Dijksterhuis & Nordgren, 2006); it can overshadow adaptive memory processes (Schooler & Engstler-Schooler, 1990). In addition, conscious reflection hardly seems to help Mindful attention 55 people predict what they will truly enjoy in the future (Gilbert & Wilson, 2009).…”
Section: Mindful Attention In Social Psychologymentioning
confidence: 99%
“…In many subsequent studies, Wilson (2002) and Schooler et al (1993) have observed that the introspective act itself can change preferences or other mental representations being scrutinized and can do so in undesirable ways. In one study (Wilson et al, 1993), when individuals were asked to introspect on their reasons for liking or disliking two art prints before choosing one to keep and take home, they were more likely to make a choice that they would later regret, compared to those who had not introspected. Why this effect occurs is still unclear.…”
Section: Reflective Social Cognitionmentioning
confidence: 99%